Pelaksanaan Konversi Tanah Bekas Milik Adat Di Kecamatan Tegallalang Berdasarkan Peraturan Pemerintah Nomor 24 Tahun 1997. - tio maharyanto (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2017)
ABSTRACT CONVERSION OF INDIGENOUS LAND PROPERTY USED IN District TEGALLALANG UNDER GOVERNMENT REGULATION NUMBER 24 OF 1997 With the promulgation of Law Nomor 5 of 1960, land rights are subject to the Law of the West and rights over land subject to the Customary Law converted (modified rights) to land rights according to Law Nomor 5 of 1960, Law Nomor 5 1960 stipulates that holders of rights over land subject to the Law of the West given the oPeraturan Pemerintahortunity for 20 (twenty) years since the promulgation of Law Nomor 5 of 1960 until September 24 1980.Konversi land rights is a change in the status of land rights according to the law long before the enactment of the Agrarian Law. In principle, this conversion occurs from land rights to land rights, instead of the right to control the state of land to land rights. Conversion over land rights are subject to the Customary Law (rights Indonesia) originally stipulated in the Minister of Agriculture and Agrarian Nomor 2 of 1962 on the affirmation of the conversion and Pendaftaran Former Indonesian Rights to Land. At this time, the conversion of the former rights of Indonesia conducted in a systematic way pendaftaran soil and ground pendaftaran sporadic. Keywords: Owned Used Indigenous Land, Conversion and Property Rights